Analisis Struktur dan Kaidah Kebahasaan pada Kumpulan 5 Naskah Drama Pemenang Sayembara serta Pemanfaatannya Sebagai Bahan Ajar Di Mts - Khoirunnisa, Khoirunnisa (Jurnal Artikula, 2025)
This study aims to describe the structure and linguistic rules in a collection of 5 drama scripts that won the competition and their use as teaching materials in MTS. Researchers analyzed the structure and linguistic rules in depth using descriptive qualitative methods. Data sources were obtained through reading and note-taking methods and then analyzed using the theory of intrinsic structure by Mardelina. The theory of intrinsic structure consists of theme, message, plot, character, dialogue, background, language, interpretation. And the rules of language by Kosasi and Kurnia which consist of chronological conjunctions, verbs describing events, verbs describing feelings and thoughts, and words that use nature, atmosphere, characters, places. Based on the results of the description of the analysis of the structure and linguistic rules in a collection of 5 drama scripts that won the competition, there are elements of theme, message, plot, character, dialogue, background, language, interpretation and chronological conjunctions, verbs describing events, verbs describing feelings and thoughts, and words that use nature, atmosphere, characters, places. This study is recommended to be considered as a reference material to improve students' abilities in appreciating literary works, especially drama scripts, and can improve literature teaching in schools.